Évaluation de l’amélioration du Comité pastoral suite à l’intervention d’AICCRA: Vers un bulletin modernisé, participatif et de diffusion multi-canaux - Sarr, Mamadou Adama; Diedhiou, Lamine (International Livestock Research Institute, 2025)
The Pastoral Committee (PC), coordinated by DIREL, produces a monthly bulletin on the livestock situation in Senegal. Thanks to support from the AICCRA project, its operation and content have been modernized: a more concise format, harmonization of contributions, integration of digital tools, and expansion of partnerships. The bulletin is now clearer, more interactive, and more relevant for stakeholders in the sector. However, challenges remain regarding the dissemination of information and linguistic adaptation for the target audience.